Chemical Mechanical Planarization of Ruthenium Using Sodium Hypochlorite Based Titania Slurry. (1st January 2017) - Yadav, Kavita; Manivannan, R.; Victoria, S. Noyel
Abstract : In the present work, chemical mechanical planarization (CMP) of Ru and Cu was carried out using titania based slurry containing sodium hypochlorite (NaOCl) as oxidizer with and without benzotriazole (BTA) as corrosion inhibitor. The CMP results reveal that in the absence of BTA, Ru removal rate (RR) increases with pH until pH 7 and then decreases gradually in the alkaline region, while Cu RR decreases with increase in pH. In the presence of BTA, both Cu and Ru removal rates decreased while the same trend in RR was observed with change in pH. RR selectivity between Ru and Cu of 1 was obtained at pH 9 which is preferred in industries. In the presence of NaOCl, Ru oxidizes to form RuO4, in the acidic and neutral pH and RuO4 − and RuO4 2− in alkaline pH, which aids in the formation of RuO3 /RuO2 . The electrochemical techniques were also employed to understand the removal mechanism of Ru and Cu in electrolyte containing NaOCl with and without BTA. The I corr values of Ru and Cu, obtained from the extrapolation of Tafel curves, follow the CMP removal rate trend. An electrical equivalent circuit was proposed to explain the results obtained in electrochemical impedance spectroscopy studies.